MEMBANGUN MANAJEMEN KEMANDIRIAN EKONOMI SANTRI MELALUI INOVASI DAN KREATIVITAS KEWIRAUSAHAAN DI PESANTREN UMMUL QURO - Mahmudi, Mahmudi; Savitri, Enny; Hindriari, Reni (LAP4B, 2026)
The Community Service Program (PKM) implements a comprehensive approach in building student economic independence management through the development of innovation and entrepreneurial creativity at the Ummul Quro Islamic Boarding School, responding to global challenges where creativity, innovation, and entrepreneurship are emphasized as the main force in encouraging the development of a rapidly changing world. This study uses a qualitative method with an ethnographic approach involving 45 students and ustadz for an intensive four-month period, combining experience-based entrepreneurship training with Business Model Canvas workshops and experience sharing activities with successful entrepreneurs of pesantren alumni. The results of the program showed a significant transformation in the creative thinking skills of students which increased by 72%, the development of 28 innovative product prototypes, and the formation of 12 new business units with a sustainable business approach. This program contributes to the achievement of SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure), strengthening the positioning of implementing universities in the Times Higher Education Impact Rankings through measurable and far-reaching community engagement.